Favorable outcome in cerebral abscesses caused by Citrobacter koseri in a newborn infant. Issue 1 (2015) - Algubaisi, Sarah; Bührer, Christoph; Thomale, Ulrich-Wilhelm; Spors, Birgit
Abstract: The treatment of brain abscesses in newborn infants is controversial. We report on a 6-week-old infant with multiple brain abscesses caused by Citrobacter koseri that resolved after treatment with combined surgical drainage and intravenous therapy with meropenem and fosfomycin.